Polysensitization in Contact Allergy in Benin: Study of Three Cases - ADEGBIDI, HUGUES DANIEL GBADEBO (My University, 2017)
Introduction: Periodically updated (from 23 to 28 allergens), the European baseline series (EBS), first introduced in France in 1980, is an indispensable tool for the exploration of contact allergy. Patients with multiple contact allergies, also referred to as polysensitized, are more frequent than predicted from prevalence of single sensitivities. Observations: There were three cases of patch tests carried out respectively in a 3 ½ years, a 37 year old woman and a man of 53 years. All three patients had polysensitization six contact allergens. Discussion: This is a first study conducted in Benin on allergenic polysensitization. These three cases show that polysensitization can be seen in the child as well as the adult on the one hand, and in both sexes on the other.
Keywords: Contact allergy; Patch tests; Polysensitization; Benin